Five terms fighting for last four spots - New Straits Times, Ajitpal Singh (2010)
Universiti Tunku abdul Rahman (UTAR) recorded back-to-back victories in the Uni Colege Basketball League (UCBL) at the UPM Indoor Basketball Court in Serdang last weekend.